Certain Triple Integral Relations Involving Multivariate H-Function - V. B. L. Chaurasia; Vishal Saxena (Scientia Series A: Mathematical Sciences, 2025)
The aim of this paper is to evaluate certain triple integral relations involving H-function and the multivariable H-function. Next, we give three Theorems containing the product of H-function, with the help of our main findings and using the Mellin integral transform. The results obtained here are quite general in nature due to the presence of functions which are basic in nature. A large number of new results have been obtained by proper choice of parameter.
Keywords: Lauricella Function; Multivariable H- functions; Mellin transform.